2017
DOI: 10.1111/afe.12226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape cover and local habitat characteristics on visiting bees in tropical orchards

Abstract: 1 Global population declines of insect pollinators highlight the need for a greater ecological understanding of the responses of wild pollinators to local management actions and to human alterations of landscapes, especially in the tropics where crops are highly dependent on wild pollinators. 2 We examined the effects of local and landscape factors on the richness and abundance of bees in farms around Bangkok, Thailand. Bee communities in 24 mango (Mangifera indica L.) orchards in heavily modified landscapes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 96 publications
6
15
0
Order By: Relevance
“…Our findings may show that JHB may be successfully exploiting the diverse nectar sources available to them in these environments. This may suggest that Japanese urban landscapes are not as detrimental to JHB as western urban environments are to WHB, as found in existing studies that have explored the impact of urban environments on pollen forage and pollinator health [43,61,62]. Few studies have explicitly studied the link between landscape "quality" and nectar foraging as has been attempted in our study.…”
Section: Could Urban Land Use Be Less Detrimental?supporting
confidence: 58%
“…Our findings may show that JHB may be successfully exploiting the diverse nectar sources available to them in these environments. This may suggest that Japanese urban landscapes are not as detrimental to JHB as western urban environments are to WHB, as found in existing studies that have explored the impact of urban environments on pollen forage and pollinator health [43,61,62]. Few studies have explicitly studied the link between landscape "quality" and nectar foraging as has been attempted in our study.…”
Section: Could Urban Land Use Be Less Detrimental?supporting
confidence: 58%
“…Our findings may show that Japanese honeybee could be successfully exploiting the diverse nectar sources available to them in these environments. This may suggest that Japanese urban landscapes are not as detrimental to Japanese honeybee as western urban environments are to Western honeybee, as found in existing studies that have explored the impact of urban environments on pollen forage and pollinator health [50,62,63]. Few studies have explicitly studied the link between landscape "quality" and nectar foraging as has been attempted in our study.…”
Section: Could Urban Land Use Be Less Detrimental?supporting
confidence: 53%
“…The significantly positive correlation between bee species' abundance, richness and evenness in savannas and cotton fields but not in sesame fields indicates that both crop types differed regarding their attractiveness to bees or that the surrounding landscape affected bee communities of cotton and sesame fields not consistently (Williams & Winfree, 2013). In a study of landscape effects on bees in Mango ( Mangifera indica L.) orchards in central Thailand, the authors reported that characteristics of the overall bee community were associated more with farm scale factors than with landscape factors (Tangtorwongsakul, Warrit, & Gale, 2018). Hence, our results show that depending on crop type, bee communities of savanna habitats can impact bee community structure in agricultural fields and vice versa (Klein, Steffan‐Dewenter, & Tscharntke, 2003b; Ricketts, 2004).…”
Section: Discussionmentioning
confidence: 99%